Analysis of Barriers to the Implementation of Circular Economy Principles in the Plastics Industry: A Best-Worst Method Approach - Pinheiro, Mariana Fonseca (2022)
Dissertação de Mestrado em Engenharia e Gestão Industrial apresentada à Faculdade de Ciências e Tecnologia